ANALISIS INTERPRETASI SISWA KELAS XI SMA NEGERI 3 PALU TERHADAP GRAFIK NUMERIK GLB-GLBB - Toding, Stevany; Mansyur , Jusman; Darsikin (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aims to analyze the interpretation of class XI MIA 1 students at SMA Negeri 3 Palu on numerical graphs on GLB and GLBB material. This study used a qualitative descriptive method which was carried out on students of class XI MIA 1 SMA Negeri 3 Palu. Sampling was done by means of purposive sampling/consideration. The data in this study were collected through observation, written tests in the form of descriptions, and interviews. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. Based on the results of data analysis, there are several difficulties when interpreting graphs, namely: (1) interpreting a combination of several numerical graphs, (2) interpreting numerical graphs by connecting graphs with physical concepts, (3) interpreting the acceleration of objects on a velocity versus time graph, (4) interprets an object that moves backward until it stops but the line graph goes up, (5) determines the motion of an object on a numerical graph of two objects in one numerical graph.